Co-Production Of Silica And Other Commodities From Geothermal Fluids - William Bourcier (The Minerals, Metals and Materials Society, 2006)
Geothermal Brines are a significant potential source of valuable minerals and metals. These brines are water that is heated by the natural heat flow from the depths of the earth. Hotter brines, typically with temperatures greater than 120°C, are used to generate electricity. Lower temperature brines are directly used to supply thermal energy to applications such as agriculture, aquaculture and process/domestic heat. The geothermal waters have had intimate and lengthy contact with the layers of the earth?s crust that they flow through, resulting in dissolution of minerals and metals from the rocks, and solution into the hot water. These aqueous solutions can be processed to recover minerals and metals. Some potential products include silica, zinc and lithium, along with other materials. Recovery of minerals and metals from geothermal brines can be viewed as ?solution mining by nature?, followed by application of known or new hydrometallurgical techniques for isolation and purification. This paper discusses the opportunities, the processes, the challenges, the current status, the economics and the potential for recovery of minerals and metals from geothermal brines.